Studying Spatial Visual Attention: The Attention-Window Task as a Measurement Tool for the Shape and Maximum Spread of the Attention Window - Klatt, Stefanie; Memmert, Daniel (Frontiers in Psychology, 2021)
Visual attentional processes have been an important topic in psychological research for years. Over the last few decades, new methods have been developed, aiming to explore the characteristics of the focus of attention in more detail. Studies which applied the “Attention-Window Task” (AWT), quantified the maximum extent of the “Attention Window” (AW) along its horizontal, vertical, and diagonal meridians, when subjects were required to perceive two peripheral stimuli simultaneously. In three experiments using the AWT, we investigated the effects of cue validity (Experiment 1), stimulus-onset asynchrony (SOA, i.e. the interval between the onset of the cues and the onset of the target stimuli), and target stimuli complexity (Experiment 3) on the size and shape of the AW. Results showed that the AW was greater under valid cue conditions compared to invalid conditions, when the locations of cue and target stimuli differed. Furthermore, the AW decreased when the SOA between the cue and targets was reduced and also when the task complexity was higher and more objects within the target stimuli had to be classified. Overall, it can be stated that the AWT with its possible task changes and adjustments can be considered as a potential standard tool to measure the maximum spread and shape of the spatial AW.